COMPARATIVE ANALYSIS OF THE EFFECTS OF CDS, OVX AND VIX INDICES ON BRICS AND MIST COUNTRY STOCK INDICES (Third Sector Social Economic Review, 2023)
Many studies in recent years have shown that stock markets exhibit more volatility than developed markets, especially when emerging economies are exposed to external shocks. In this study, the joint behavior of CDS, VIX, OVX and stock markets is investigated by focusing on BRICS and MIST countries from developed countries. In the study covering the period between December 2010 and June 2021, a moderator effect model panel data analysis was conducted and it was observed that the effects of CDS, VIX and OVX indices differed in BRICS and MIST countries. As a result of the analysis, it is also determined that the index with the highest impact on stock market indices is the OVX Index and the indicator with the least impact is the CDS. According to the findings of the study, policymakers and investors who include the investment instruments of such country groups in their portfolios are advised to take into account their responses to volatility as an important risk factor among other risks.
Keywords: Volatility Index (VIX); Oil Volatility Index (OVX); Credit Default Swaps (CDS); BRICS and MIST countries; Panel Data Analysis